Exploring Indicators and Developing the Initial DigiGOVQUAL Model: An Exploratory Factor Analysis in Banjar City - Hudzaifah Nuruzzaman Ramdhani; Refi Rifaldi Windya Giri (International Journal of Artificial Intelligence Research, 2025)
The digital transformation of government through the Electronic-Based Government System (Sistem Pemerintahan Berbasis Elektronik—SPBE) has become a foundational element of bureaucratic reform in Indonesia. However, the absence of a standardized instrument for assessing SPBE service quality—particularly within the Government-to-Government (G2G) domain—has hindered systematic evaluation and continuous improvement efforts. This study aims to develop a preliminary model called DigiGOVQUAL, designed to measure the quality of SPBE services from the perspective of internal users within government institutions. The model adapts and refines relevant indicators from the E-Government Service Quality (EGSQUAL) framework to better reflect the specific characteristics of digital public services in the Indonesian bureaucratic context. Employing a quantitative research approach, the study utilizes Exploratory Factor Analysis (EFA) to validate the construct dimensions. Data were collected via an online survey distributed to over 200 active civil servants in the Banjar City government who have experience using G2G SPBE services. The findings are expected to contribute to the development of a valid and contextually appropriate evaluation tool for digital government service quality. Ultimately, the DigiGOVQUAL model is intended to support more accountable and user-centered public service delivery policies in the digital era